A comparative statistical study on water pollution before and during pushkaralu in Tungabhadra-2020 River in Kurnool (urban), AP, India (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Humans are creatures who believe in higher entities. In a land like India which has multiple cultures and religions, some practices may cause harm to the environment. Pushkaralu is a festival that taken place on the bank of a river according to the zodiac sign in Hindu mythology. The year 2020 was the year for the river of Tungabhadra and as it is a year of pandemic, many things have changed regarding mass gatherings and even more regarding mass bathings. Though there were many norms to be followed, the mass gatherings affected the quality of water and as Kurnool town being one of the hotspots for covid-19 and pushkaralu simultaneously.